Detection by real-time PCR and pyrosequencing of the cry1Ab and cry1Ac genes introduced in genetically modified (GM) constructs. Issue 8 (3rd August 2017) - Debode, Frederic; Janssen, Eric; Bragard, Claude; Berben, Gilbert
ABSTRACT: The presence of genetically modified organisms (GMOs) in food and feed is mainly detected by the use of targets focusing on promoters and terminators. As some genes are frequently used in genetically modified (GM) construction, they also constitute excellent screening elements and their use is increasing. In this paper we propose a new target for the detection of cry 1Ab and cry 1Ac genes by real-time polymerase chain reaction (PCR) and pyrosequencing. The specificity, sensitivity and robustness of the real-time PCR method were tested following the recommendations of international guidelines and the method met the expected performance criteria. This paper also shows how the robustness testing was assessed. This new cry 1Ab/Ac method can provide a positive signal with a larger number of GM events than do the other existing methods using double dye-probes. The method permits the analysis of results with less ambiguity than the SYBRGreen method recommended by the European Reference Laboratory (EURL) GM Food and Feed (GMFF). A pyrosequencing method was also developed to gain additional information thanks to the sequence of the amplicon. This method of sequencing-by-synthesis can determine the sequence between the primers used for PCR. Pyrosequencing showed that the sequences internal to the primers present differences following the GM events considered and three different sequences were observed. The sensitivity of the pyrosequencing was tested on reference flours with a low percentage GM content and different copy numbers. Improvements in the pyrosequencing protocol provided correct sequences with 50 copies of the target. Below this copy number, the quality of the sequence was more random.